Introduction to Actuarial Science and the Actuary Profession at SMA PRAMITA Tangerang - F. Anthon Pangruruk (Jurnal Pengabdian Masyarakat Bestari, 2022)
Actuarial science is a science that applies mathematical and statistical science methods to assess risk. Currently actuaries are needed with large income. But ironically, many high school students do not know the knowledge and profession of actuaries. Community service activities are carried out as an actualization of knowledge from the Statistics Study Program at Matana University through an introductory seminar on actuarial science and the actuary profession given to Class X students of PRAMITA SMA Tangerang. Community service can be carried out very well. Positive responses from all seminar participants included the level of satisfaction (satisfied 11.6%, very satisfied 46.5% and very satisfied 41.9%), the usefulness of the event (100% useful), and the quality of the program (9.3 % good, 39.5% very good, 51.2% very good). This PKM activity is an implementation of the Mathematical Finance and Insurance Mathematics courses.